2014
DOI: 10.5771/0943-7444-2014-2-160
|View full text |Cite
|
Sign up to set email alerts
|

Classifying for Social Diversity

Abstract: His research has long focused on facilitating interdisciplinary research and teaching. He is president of the Association for Interdisciplinary Studies. Knowledge organization has become the dominant element in that research agenda, and he has authored two books and several articles that develop classifications of things studied, theories and methods applied, types of data, ethical perspectives, research practices, and relationships. He has contributed to the Integrative Levels Classification and is developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In the latter article, she draws on feminist philosophy in order to urge an approach to classification that relies less upon hierarchy and more on a web of relationships. I have recently (Szostak 2014a) shown that the sort of approach discussed in this paper fits Olson's criteria and responds to many particular concerns she raises.…”
Section: Philosophy Through Information Sciencementioning
confidence: 77%
See 3 more Smart Citations
“…In the latter article, she draws on feminist philosophy in order to urge an approach to classification that relies less upon hierarchy and more on a web of relationships. I have recently (Szostak 2014a) shown that the sort of approach discussed in this paper fits Olson's criteria and responds to many particular concerns she raises.…”
Section: Philosophy Through Information Sciencementioning
confidence: 77%
“…The classification evaluated here has been evaluated (favorably) with respect to other criteria as well (see Szostak, 2014a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…-As argued above, the disagreements between individuals or groups about the meanings attached to complex/contested terms can be greatly alleviated by breaking these into basic terminology around which a much greater degree of consensus can be achieved. -Disagreements regarding the nature of classes can be alleviated by limiting the use of hierarchy, and also by pursuing a synthetic approach (Szostak 2014). -Individuals or groups also disagree regarding which causal relationships (where "causal" is defined broadly to indicate any influence that any thing may exert on any other) are most important or the nature of particular causal relationship.…”
Section: Letter To the Editormentioning
confidence: 99%